If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 6 = 7x + 6 Reorder the terms: 6 + 12x = 7x + 6 Reorder the terms: 6 + 12x = 6 + 7x Add '-6' to each side of the equation. 6 + -6 + 12x = 6 + -6 + 7x Combine like terms: 6 + -6 = 0 0 + 12x = 6 + -6 + 7x 12x = 6 + -6 + 7x Combine like terms: 6 + -6 = 0 12x = 0 + 7x 12x = 7x Solving 12x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12x + -7x = 7x + -7x Combine like terms: 12x + -7x = 5x 5x = 7x + -7x Combine like terms: 7x + -7x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 3+4x=2x+-1 | | 4.9a=49 | | 5*365= | | -5x-7=-6-3 | | 2(x+3)5-x-12=2 | | (4/12)(9/12)=x | | x-17=82 | | d-14=12 | | 4(x+4)=5+4x | | 4x+3=2x+-1 | | x+32=93 | | 2y-2=3y+3 | | x/3=x-22 | | 7y+3+=12y-2 | | 5x^2-7x+12=3 | | z+24=76 | | 1,000+25n-300=740+32n-320 | | 20+.05m=15+.25m | | 2x+12=4(x+3)-2x | | 35(6/10) | | 11=35-2 | | 219-6x=30x+15 | | (16/10)=(24/x) | | 4w+3w-6w=w-15+2w-3w | | 14/2=12/x | | (18/12)=(3x/16) | | -1=32-16+t | | 10(x+3)=8x-14 | | 3x=183 | | 4u=256 | | 4w+3w-6w=w-15+2w-w | | 12-3x=51 |